GENDER-BASED MATHEMATICAL COMMUNICATION SKILLS: SYSTEMATIC LITERATURE REVIEW - Usman, Muhammad Rizal (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
The purpose of this study is to study literature related to differences in mathematical communication skills of high school students based on gender. The study uses the method of Systematic Literature Review (SLR) which is carried out through the process of identification, evaluation, and interpretation of all available research evidence with the object of the research is student mathematics communication skills and Gender. Design used is to summarize, review, and analyze 9 articles that are highly relevant to the subject of the study. The article used is an article in a journal accredited by Sinta. The results of this Systematic Literatur Review show that there is a difference in the ability to communicate mathematically between male and female students. Differences in mathematical communication skills between male and female students can be caused by a variety of factors, such as biological, social, and cultural factors. The way students process and understand mathematics can be influenced by biological factors, like differences in brain structures.